Peran Badan Pengawasan Pemilu Dalam Penanggulangan Pelanggaran Pemilihan Umum di Era Digital Dalam Persfektif Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum - Muhamad Raihan Husaini; Nispi Aliyatunnisa; Nurul Aini; Resti Marliasari; Zenal Syaepul Rohman (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The Election Supervisory Body (Bawaslu) has a crucial role in ensuring the sustainability of democracy and the validity of general election results. In the digital era, technology has an influential role in facilitating the process of socialization regarding election schedules and programs, and can increase people's knowledge, understanding and awareness of their rights and responsibilities in elections. In its use, it is hoped that it can simplify the work of election organizers and provide access to information, transparency and accountability to the public as part of professional and trustworthy public services. This supervisory function and task is very important to ensure that the election implementation process remains in accordance with the principles and principles of election administration. Supervision Model in the Digital Era in General Elections, in this case, public participation is mandatory at every stage of the election/general election. The problems and efforts in implementing general election supervision in the digital era are the role of the Election Supervisory Agency (Bawaslu) in supervising elections and this is also inseparable from criticism from election participants and the general public. This condition was motivated by dissatisfaction with Bawaslu's performance in supervising the elections.